Effects of a 4-week intervention using semi-custom insoles on perceived pain and patellofemoral loading in targeted subgroups of recreational runners with patellofemoral pain. (November 2018) - Sinclair, Jonathan; Janssen, Jessie; Richards, Jim David; Butters, Bobbie; Taylor, Paul John; Hobbs, Sarah Jane
Abstract: Objective: Explore the effects of a 4-week intervention using semi-custom insoles in recreational runners with patellofemoral pain. Design: Mixed methods. Participants: Seventeen (10 males and 7 females) recreational runners. Setting: Laboratory . Outcome measurements: Participants were separated into specific subgroups, then provided with a pair of semi-custom insoles, for a period of 4-weeks. Lower extremity kinetics/kinematics during running at 4.0 m/s were obtained. In addition, knee pain was examined using the Knee injury and Osteoarthritis Outcome Score-Patellofemoral scale (KOOS-PF). Data were collected before and after wearing the insoles for 4-weeks. Results: Significant improvements were shown for KOOS-PF in both subgroups (strong: (pre) = 63.84 & (post) = 71.49 and weak and tight: (pre) = 53.03 & (post) = 72.73), although only improvements in the weak and tight group exceeded the minimum clinically important difference (MCID). In addition, significant reductions in peak patellofemoral stress were shown in both subgroups (strong: (pre) = 6.82 & (post) = 6.39KPa/BW and weak and tight: (pre) = 7.66 & (post) = 6.28KPa/BW), although only reductions in the weak and tight group exceeded the MCID. Conclusions: Semi-custom insoles may be a mechanism to reduce patellofemoral pain symptoms in recreational runners from the weak and tight subgroup. It is proposed that this improvement was mediated through reductions in patellofemoral loading in this subgroup. Highlights: First intervention to examine semi-custom orthoses in runners with patellofemoral pain. First study to examine the effects of conservative treatments in different subgroups. Examination of psychological wellbeing alongside self-reported pain symptoms is also provided.